Guidance: The practical management of the gastrointestinal symptoms of pelvic radiation disease. Issue 1 (17th June 2014) - Andreyev, H Jervoise N; Muls, Ann C; Norton, Christine; Ralph, Charlotte; Watson, Lorraine; Shaw, Clare; Lindsay, James O
Abstract : Background: A recent randomised trial suggested that an algorithmic approach to investigating and managing gastrointestinal symptoms of pelvic radiation disease (PRD) is beneficial and that specially trained nurses can manage patients as effectively as a gastroenterologist. Aims: The aim of the development and peer review of the guide was to make the algorithm used in the trial accessible to all levels of clinician. Methods: Experts who manage patients with PRD were asked to review the guide, rating each section for agreement with the recommended measures and suggesting amendments if necessary. Specific comments were discussed and incorporated as appropriate, and this process was repeated for a second round of review. Results: 34 gastroenterologists, 10 nurses, 9 dietitians, 7 surgeons and 5 clinical oncologists participated in round one. Consensus (defined prospectively as 60% or more panellists selecting 'strongly agree' or 'agree') was reached for 27 of the original 28 sections in the guide, with a median of 75% of panellists agreeing with each section. 86% of panellists agreed that the guide was acceptable for publication or acceptable with minor revisions. 55 of the original 65 panellists participated in round two. 89% agreed it was acceptable for publication after the first revision. Further minor amendments were made in response to round two. Conclusions: Development of the guide in response to feedback included ▸ improvement of occasional algorithmic steps ▸ a more user-friendly layout ▸ clearer timeframes for referral to other teams ▸ expansion of reference list ▸ addition of procedures to the appendix.